Effectiveness of Fiscal and Economic Policy in Monitoring Inflation in Nigeria - Okeke, Chinenye (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigates the effectiveness of monetary and fiscal policies in controlling inflation in Nigeria from 1993 to 2023. Using co-integration and error correction methods on yearly time series data, the study reveals several key findings. The unit root test indicates that only inflation (INF) is stationary at levels, while money supply (MS), taxation (TAX), and government expenditures (GEX) are stationary at first difference. The results show that an increase in the money supply and government expenditures lead to a rise in the inflation rate, whereas higher taxation reduces it. Based on these findings, the study concludes that MS, TAX, and GEX significantly impact on inflation in Nigeria. The study recommends that policymakers should better manage the money supply to reduce the inflation rate by decreasing the amount of money in the economy. Increasing the tax rates on individuals and companies, especially during periods of high inflation, can lower the amount of spendable money among citizens, thereby reducing inflation. Lastly, the government should control its expenditures to decrease the total amount of money in circulation, effectively reducing the country's inflation rate.